Factor affecting foreign direct investment in Malaysia / Syarifah Nur Aimy Al-Wafa Syed Ahmad Afandi - Syed Ahmad Afandi, Syarifah Nur Aimy Al-Wafa (2021)
Foreign Direct Investment (FDI) plays a crucial role in increasing a country's development and economic growth. In developing countries, as they face capital shortages in their development process, they depend on FDI to encourage their economy. The strong growth performance of the Malaysian economy depends heavily on FDI. FDI generates economic growth by increasing capital formation through the expansion of production capacity, promotion of export and creation of employment in Malaysia. The researchers' attention to examine the factors affecting FDI inflows in Malaysia by using the annual data from year 1970 until 2019. Multiple linear regressions model is applied to study the relationship between independent variables and dependent variable. The results of the study show that gross domestic product and exports have significantly and positively affect FDI inflows. Other than that, external debt also significantly affects FDI inflows but its relation with FDI is negative. Imports are the final goods and its relationship with the FDI inflow is negative. It is significant effect on FDI.